Al-Qur’an dan Diskursus Tentang Hate Speech - Putri, Nurfadzilla; Syafieh, Syafieh (Prodi Ilmu Al-Qur'an dan Tafsir, 2024)
Hate speech is behavior that is badmouthing, harassing, intimidating, inciting hatred or provocation against individuals and groups based on race, ethnicity, religion, gender or social orientation which has many negative impacts. This article examines the discourse regarding hate speech based on the perspective of the Qur'an using qualitative data analysis methods and a library research approach. The results of this research show that the Al-Qur'an never legitimizes hate speech behavior. The Qur'an as huda lil nas summarizes teachings that call for good communication ethics in society and condemns behavior that falls within the scope of hate speech. Strategies for dealing with hate speech behavior that can be emulated in the Al-Qur'an are Qaulan Kariman, Qaulan Layyinan, and Qaulan Sadidan.